Novel low-melting bisphthalonitrile monomers: Synthesis and their excellent adhesive performance. (15th June 2021) - Liu, Caizhao; Zhang, Bin; Sun, Mingming; Liu, Xiang; Zhang, Xugang; Li, Jianhui; Wang, Lei; Zhou, Heng
Graphical abstract: Highlights: An efficient strategy was taken to prepare bisphthalonitrile (PN) monomers with low-melting point. The introduction of asymmetric structure improves the processability and adhesive properties of the PN. Glass transition temperature is mainly controlled by the crosslink density and stiffness of polymer chain. Abstract: High melting temperature of most bisphthalonitrile monomers are a challenging problem in processing, especially for the preparation of adhesives. The present work introduces the "asymmetric structure" concept to improve the processability of bisphthalonitrile. Four novel bisphthalonitrile monomers (BBPN, BCPN, BPPN, and BMPN) with relatively low melting points were synthesized by a nucleophilic substitution reaction, and FTIR, 1 H, and 13 C NMR analysis were performed for the confirmation of chemical structures. A much lower melting point and broader processing window as compared to 4, 4′-bis(3, 4-dicyanophenoxy)biphenyl (BAPh) were recorded for the synthesized monomers. Then they were cured by using 8 wt% of p-phenylenediamine (p-PD) as a curing agent, and backbone structures of monomers played a vital role in the glass transition temperature ( Tg ) and recorded in between 255 and 311 °C. The incorporation of asymmetric structure results in an amazing adhesive performance, which is comparable with commercial polyimides but coupled with a thermal stability tradeoff.